Sensitivity of Torch Ginger and Basil Extracts Against Candida sp. from Vaginal Discharge Samples - Arelliza, Fatma Sheilla; Nugroho, Yusuf Eko; Faizal, Imam Agus (poltekkes kemenkes pontianak, 2025)
Pathological vaginal discharge is a common infection among women, often caused by the fungal species Candida albicans. The increasing resistance to synthetic antifungal agents such as ketoconazole has prompted the need for alternative herbal therapies. This study aimed to identify the presence of Candida albicans in vaginal swab samples from female D4 TLM UNAIC students an to assess the antifungal activity of combined extracts of kecombrang flower (Etlingera elatior) and basil leaves (Ocimum basilicum) prepared using the infusion method. An experimental design was used with the well diffusion method to measure inhibition zones at extract concentration of 50%, 70%, and 90%. The results showed that 31% of the 48 samples tested positive for Candida albicans. Macroscopically, the colonies appeared white to cream, convex, and had a characteristic yeast odor, while microscopic examination revealed blastospores. The positive control group using ketoconazole exhibited strong antifungal activity with an inhibition zone diameter of 23 mm. In contrast, the combined infusion extracts at all tested concentration (50%, 70%, and 90%) showed no inhibition zones (0 mm), indicating an absence of antifungal activity. The conclusions of this research are the infusion extraction method was ineffective in isolating active antifungal compounds from the tested plants under the conditions of this study.